Innovative pedagogical conditions and technologies for improving pragmalinguistic and sociopragmatic competences in an English as an international language context - Yeshanov , Marat (The Lingua Spectrum, 2025)
The global spread of English calls for a shift from native-speaker norms to approaches that reflect English as an International Language (EIL) and its pragmatic diversity. This article critiques traditional methods for neglecting learners’ pragmalinguistic and sociopragmatic competence in intercultural communication. Drawing on variational pragmatics and World Englishes, it presents empirical evidence of pragmatic variation across English varieties and introduces the Variational and Intercultural Pragmatics (VIP) model. This innovative framework combines technology-enhanced discovery learning with metacognitive reflection to foster learner autonomy, meta-pragmatic awareness, and intercultural sensitivity. The study outlines VIP’s theoretical foundations, pedagogical application, and expected outcomes, emphasizing the need to embrace linguistic diversity as a learning goal. By shifting the focus from normative accuracy to communicative effectiveness, the VIP model empowers learners to become adaptable and strategically competent global communicators. This research advances EIL pedagogy by offering educators a structured approach to prepare students for pluricentric language use in real-world contexts.